INCIDENCIA DE INFECCIÓN DE Phytophthora palmivora EN Theobroma cacao BAJO CONDICIONES DE ESTRÉS HÍDRICO Y PRESENCIA DE RIZOBACTERIAS - Cando León, Tania Maricela (2023)
Cocoa production is mainly affected by fungal diseases, including Phytophthora palmivora. On the other hand, water stress negatively affects cocoa, reducing water and nutrient uptake. Rhizobacteria offer effective strategies to address fungal diseases and water stress conditions. The objective of the study was to determine the incidence of Phytophthora palmivora infection in Theobroma cacao under water stress conditions and the presence of rhizobacteria. Three experiments were carried out with a completely randomized DCA design.